Archiving and Re-using of Qualitative Data as a Path to Development of Public Administration Research - Gajda, Joanna (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
In response to the assumptions of new public management models and public or good governance, practical aspects of research in the area of public administration and the development possibilities of qualitative research methods are presented in the article. Due to the fact that qualitative research has become increasingly popular in the above disciplines, data archiving and transparency is discussed (Moravcsik), (Yom et al.) and guidelines and principles are established (American Political Science Association). However, there is a lot of controversy among scholars (Monroe), and some examples are missing. This paper presents the challenge of ‘openness’ in the empirical activities (or empirical practice) of researchers. Its purpose is to present the archiving data potential from in-depth interviews on the example of a small set of qualitative data from research in the field of public administration. Firstly, the basic assumptions of new models of functioning of public administration and related consequences for researchers are described. In the second part, the challenges related to openness in contemporary public administration models are briefly mentioned. Next, the method of creating an archive from existing data, individual stages, documents, and data is outlined; it is based on the author’s best practice on Qualidata (American Political Science Association; Van den Eynden et al.) and DA-RT principles.1 The summary includes examples of probable opportunities and challenges related to usage of data archiving for the research in public administration and political science development.